Análisis Financiero de la Compañía de Trasporte de carga pesada Trasnlogbas S. A. - Velásquez Montenegro, Rita Karla (2020)
The present case study: "Financial Analysis of the Transport Company of Heavy Load Trasnlogbas SA 2017 and 2018", a company dedicated to the provision of heavy road services, allows to know during its development the application of methods to analyze liquidity and profitability of the company, also provides information to determine with concrete results, the behavior of the business in the periods between 2017 - 2018. The financial study is based on indicators, to determine whether or not the company is achieving its objectives. And in turn know if the company is making progress based on the previous fiscal year. This process was carried out with the values of the different accounts of the income statement and balance sheet that are fundamental and provide the necessary information to know your situation.